Dance civet cat : child labour in the Zambezi Valley. - Reynolds, Pamela (Zed Books ; Ohio University Press, 1991)
In this, the first comprehensive study of the Tonga people in Zimbabwe, Pamela Reynolds focuses on children?s work in a subsistence agricultural system, assessing how much work they do, the value of their work to their families and how it both limits their opportunities and fosters their personal growth and knowledge. Set in the context of the history of the Tonga people south of the Zambezi river and a discussion of their current position as a minority group in independent Zimbabwe, this is a study of social differentiation, particularly the impact of gender and age, and of the individual as a social agent. Based on extensive fieldwork among the Tonga, it avoids the usual trap of analyzing children?s labour roles in isolation from social, economic and political factors -- Présentation de l'éditeur.